1988
DOI: 10.1002/macp.1988.021890523
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of methyl acrylate photoinitiated by 4‐dimethylamino‐4′‐isopropylbenzophenone

Abstract: The initial rate of the polymerization of methyl acrylate photoinitiated by Cdimethylamino-4'-isopropylbenzophenone (2) varies linearly with monomer concentration and the square-root of light intensity. For small absorbances, the initial polymerization rate, %, varies linearly with the square-root of the photoinitiator concentration. For high absorbance values, I$ is independent of the photoinitiator concentration in a well-stirred system and decreases as the photoinitiator concentration increases in an unstir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Presentation of their results in terms of position and time variables with arbitrary units, and the lack of a closed-form solution (i.e., our eq 15 for the photoinitiator concentration distribution and the analogue of (20a) for the photoinitiation rate) hinders interpretation and use. From (24), we see that for τ g ln 2 the maximum concentration occurs at y ) ln(e τ -1) and that the half-width at half of the maximum rate is (∆y) hwhm ) 2.0634. Comparison to Figure 4 of ref 23 shows that the half-width at half-maximum in that figure is about 8.41 (in "arbitrary units"), and the maximum in the volumetric photon absorption rate at each time shown (also in "arbitrary units") is at a position whose coordinate (in "arbitrary units") is numerically almost equal to the time.…”
Section: S(zs H ) )mentioning
confidence: 92%
See 3 more Smart Citations
“…Presentation of their results in terms of position and time variables with arbitrary units, and the lack of a closed-form solution (i.e., our eq 15 for the photoinitiator concentration distribution and the analogue of (20a) for the photoinitiation rate) hinders interpretation and use. From (24), we see that for τ g ln 2 the maximum concentration occurs at y ) ln(e τ -1) and that the half-width at half of the maximum rate is (∆y) hwhm ) 2.0634. Comparison to Figure 4 of ref 23 shows that the half-width at half-maximum in that figure is about 8.41 (in "arbitrary units"), and the maximum in the volumetric photon absorption rate at each time shown (also in "arbitrary units") is at a position whose coordinate (in "arbitrary units") is numerically almost equal to the time.…”
Section: S(zs H ) )mentioning
confidence: 92%
“…The expression given for R p in eq 3-65 of Odian 26 has dimensions inconsistent with those for the same symbol used elsewhere in that work. Incorrect expressions given by Mateo et al 24 for R p are dimensionally inconsistent with each other (cf. their eqs 1 and 2 and their eqs 2 and 3).…”
Section: I(xt)mentioning
confidence: 98%
See 2 more Smart Citations
“…The lower gel fractions of the PHU films crosslinked in the presence of 15 wt.-% of TPO might have resulted from the fact that absorption occurs only in the first layer of the film and the crosslinking rate is lower than that at lower concentrations where light absorption takes place throughout the film. [17,18] Infrared spectra of PHU irradiated for different periods of time with TPO (3 wt.-%) showed that the absorption peaks due to vinyl groups at 911 and 1640 cm -1 decreased with irradiation time indicating that the photocrosslinking of PHU proceeded at the expense of the vinyl groups. TGA traces of native PHU were virtually identical to that of crosslinked PHU while DSC analysis showed that the glass transition temperature increased from -51 to -46 8C when PHU was irradiated for 60 s with a medium pressure mercury lamp.…”
Section: Resultsmentioning
confidence: 99%